lebih Teknologi Membran Nanofiltrasi Terhadap Pengolahan Masalah Perairan: Review - Syifa Aulia Permata Sari; Lesta Lesta; Syarmila Syarmila; Yunilita Hanum; Zulfa Mawaddah; Jurian Jurian; Nurhadini Nurhadini (Department of Chemistry - Universitas Bangka Belitung, 2022)
One of the most widely used membranes is the nanofiltration membrane, this membrane is formed from various nanomaterials, such as metal nanoparticles and metal oxides, carbon-based nanoparticles, metal organic frameworks, and micro or organic nanoparticles. Membrane separation processes are used to concentrate or fractionate liquids to produce two liquids with different compositions. This makes the nanofiltration process an alternative compared to conventional processes. The potential of nanofiltration membranes can be used in textile industry wastewater treatment, tofu liquid waste, tofu liquid waste treatment, batik wastewater testing, and groundwater management as drinking water. In addition, nanofiltration membrane technology can be used as a separator for a substance in the air, such as removal of cypermethrin, arsenic cream, concentration of lactic acid bacteria as a tasty probiotic, removal of carbosulfan, Zr-Hf separation, and can see the characterization and performance evaluation of the antifouling properties of membranes. . Based on the process, the performance of a membrane is determined by two simple factors, namely flux (permeate flow rate) and membrane selectivity.